2021
DOI: 10.3390/cancers13164077
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Analysis of CT Images Reveals High-Grade Pathological Features to Predict Survival in Lung Adenocarcinoma

Abstract: We aimed to develop a deep learning (DL) model for predicting high-grade patterns in lung adenocarcinomas (ADC) and to assess the prognostic performance of model in advanced lung cancer patients who underwent neoadjuvant or definitive concurrent chemoradiation therapy (CCRT). We included 275 patients with 290 early lung ADCs from an ongoing prospective clinical trial in the training dataset, which we split into internal–training and internal–validation datasets. We constructed a diagnostic DL model of high-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In this study, we constructed an R-R model on the strength of radiological features integrated with radiomics features to predict the HGP of LUAD, which demonstrated an excellent predictive performance superior to previously reported omics-only models ( 18 , 19 ). The AUC value of our R-R model in the training set was 0.923, corresponding to a sensitivity of 87.0%, a specificity of 83.4%, and an accuracy of 84.2%.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, we constructed an R-R model on the strength of radiological features integrated with radiomics features to predict the HGP of LUAD, which demonstrated an excellent predictive performance superior to previously reported omics-only models ( 18 , 19 ). The AUC value of our R-R model in the training set was 0.923, corresponding to a sensitivity of 87.0%, a specificity of 83.4%, and an accuracy of 84.2%.…”
Section: Discussionmentioning
confidence: 95%
“…Our study included GGO and solid nodules, which is more aligned with the actual clinical conditions. Yeonu Choi and He et al have developed a radiomics model to predict the micropapillary and solid components of LUAD but only radiomics signatures are contained in this model (19,20). This study is the first report, as far as we know, that HGP can be predicted by a model basing on radiological features integrated with radiomics features in a relatively large dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPI may embody the characteristics of pT and histological information. Previous studies have shown that radiomic features can predict pT [28], histology [29], and grade [30] in NSCLC. PLN remained a signi cant variable in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In predicting OS, our model outperformed the pT stage and clinical model, including the pT and PLN. Previous studies have shown that radiomic features can predict pT stage [28], histology [29], pathological grade [30], and lymph vesicular invasion [37] in NSCLC. The RPI could represent more information than the clinicopathological variables; thus, it would be much more convenient to use the RPI as it can be fully automatically calculated from the CT image.…”
Section: Discussionmentioning
confidence: 99%